2014
DOI: 10.34118/jbms.v1i2.10
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hybrid steel fiber on the properties of fresh and hardened self-compacting concrete

Abstract: Self-compacting concrete (SCC) offers several economical and technical benefits, the use of steel fibers extends its possibilities. This study was performed to compare the properties of SCC and fiber reinforced self-compacting concrete (FRSCC) with high volume of mineral addition. Six mixtures were elaborated in this study. The content of the cementitious materials and the water/cementitious materials ratio were kept constant, 500 kg/m3 and 0.34 respectively.The self-compacting mixtures have been prepared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 12 publications
0
16
0
4
Order By: Relevance
“…Also, increase in the splitting tensile strength can be attributed to the reason that macro steel fiber was hooked end and longer than the other types of fibers as well as the higher modulus of elasticity. Tabatabaeian et al 5 and Haddadou et al 40 also found that long steel fibers with hooked end were more effective on the bridging of cracks.…”
Section: Resultsmentioning
confidence: 95%
“…Also, increase in the splitting tensile strength can be attributed to the reason that macro steel fiber was hooked end and longer than the other types of fibers as well as the higher modulus of elasticity. Tabatabaeian et al 5 and Haddadou et al 40 also found that long steel fibers with hooked end were more effective on the bridging of cracks.…”
Section: Resultsmentioning
confidence: 95%
“…The enhancement in splitting tensile strength could be attributed to the presence of higher content of macro steel fiber (1% by volume) as well as the inclusion of PVA fiber as microfiber. Due to having longer length and higher elastic modulus, macro steel fiber was more effective in the transfer of tensile stress resulting in the prevention of macro cracks 54 . Some researchers 17,18,55 also found that the hooked end of macro steel fiber caused the crack bridging and thus, an enhancement in the splitting tensile strength was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…This is because, long steel fibers with hooked end were more effective in the transfer of tensile stress and they had higher elastic modulus with regards to short steel fibers. Tabatabaeian et al [46] and Haddadou et al [47] also proved the effectiveness of HL on the bridging of cracks. On the other hand, adding SS into concrete led to a reduction in splitting tensile strength values for all fiber volume fractions for 7 curing days while for 28 curing days, the splitting tensile strength of SS-0.4 and SS-0.8 increased with 14.28% and 9.52%, respectively, with regards to that of control specimen.…”
Section: Effects Of Fiber Type and Shape On Splitting Tensile Strengthmentioning
confidence: 89%